2012
DOI: 10.1155/2012/301931
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Recombinant Human Endostatin on the Radiosensitivity of Human Pulmonary Adenocarcinoma A549 Cells and Its Mechanism

Abstract: We observed the effects of endostar on the radiosensitivity of pulmonary adenocarcinoma A549 cells and found that endostar inhibited A549 cell growth under normoxia and hypoxia in time and dose-dependent manners; the D0 and Dq values in control and endostar groups were (1.36 and 1.30) versus (1.019 and 1.015) under normoxia and (1.693 and 1.39) versus (2.453 and 1.026) under hypoxia, respectively; SER was 1.04 under normoxia and 1.22 under hypoxia in endostar group; under normoxia, the apoptosis rates in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Of note, the duration and intervals of endostatin and radiotherapy combinations differed in clinical trials and may affect the outcomes (as shown in Table 1). Results from preclinical studies showed that endostatin treatment could transiently normalize the tumor vasculature by reducing microvessel density and increasing pericytic coverage of the vessel endothelium, thereby providing a time window (about 1 week) to enhance the sensitivity to RT; thus, RT delivery in this period resulted in maximal anti-tumor outcomes [15,49]. CT perfusion imaging and hypoxia imaging suggested that the "time window" was within about 1 week after administration, during which endostatin improved blood perfusion and decreased hypoxia of lung cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the duration and intervals of endostatin and radiotherapy combinations differed in clinical trials and may affect the outcomes (as shown in Table 1). Results from preclinical studies showed that endostatin treatment could transiently normalize the tumor vasculature by reducing microvessel density and increasing pericytic coverage of the vessel endothelium, thereby providing a time window (about 1 week) to enhance the sensitivity to RT; thus, RT delivery in this period resulted in maximal anti-tumor outcomes [15,49]. CT perfusion imaging and hypoxia imaging suggested that the "time window" was within about 1 week after administration, during which endostatin improved blood perfusion and decreased hypoxia of lung cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,15,29,30 In our study, the patients received 3D-CRT in the IV arm and IMRT in the CIV arm. Modern techniques such as IMRT have improved target coverage using optimized modulated fields (typically [6][7][8][9][10][11][12]. IMRT might bring substantial benefits in prognosis compared to 3D-CRT.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, we initiated a prospective phase II clinical study applying an intravenous injection (IV) of Endostar with CCRT for patients with locally advanced NSCLC which showed promising survival and local control rates . Based on preclinical data the inhibition effect of Endostar on tumor cells is time‐dependent . Continuous intravenous pumping (CIV) is considered a better administration route to maintain a steady blood concentration and might improve efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations